Pengaruh Beban Pajak Tangguhan, Aktiva Pajak Tangguhan, Dan Akrual Terhadap Manajemen Laba Pada Perusahaan Aneka Industri Yang Terdaftar Di Bursa Efek Indonesia Periode 2015-2020 - Simanjuntak, Owen De Pinto (UNIVERSITAS SARI MUTIARA INDONESIA, 2021)
This study aims to determine the effect of deferred tax expense, deferred tax assets, and accruals on earnings management. The population in this study are various industrial companies listed on the Indonesia Stock Exchange for the 2015-2020 period. This research is a descriptive research with a quantitative approach. Data processing program using SPSS Version 25.By using 5 companies using purposive sampling. The data used in this study is secondary data, namely data on the financial statements of various industrial sector companies listedon the Indonesia Stock Exchange in the 2015-2020 period. The sample selection method used purposive sampling, namely the sampling method based on certain criteria. Of the 45 various industrialcompanies listed on the Indonesia Stock Exchange, there are only 5 companies that meet the research sample criteria that have been determined. The data analysis method used inthis research is multiple linear regression test, coefficient of determination (R^2) and correlation (R), partial test (t-test) and Simultaneous test (F-test) while earnings management is measured based on dummy variables. The results of this study indicate that deferred tax expense affects earnings management, deferred tax assets affect earnings management and accruals have no effect on earnings management.Based on the simultaneous test (F test) variable deferred tax expense, deferred tax assets andaccruals together have no effect on earnings management in various industrial companies listed on the Indonesia Stock Exchange in 2015-2020.